2015
DOI: 10.1111/ggi.12612
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pacemaker tele‐monitoring on quality of life, functional capacity, event detection and workload: The PONIENTE trial

Abstract: The PONIENTE trial suggests that the remote monitoring of pacemakers in older adults is an equivalent option to hospital monitoring, in terms of health-related quality of life and functional capacity. Furthermore, it allows for the early detection of clinical and pacemaker-related adverse events, and significantly reduces the number of in-hospital visits. Geriatr Gerontol Int 2016; 16: 1188-1195.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 30 publications
1
31
0
1
Order By: Relevance
“…The primary hypothesis that a telephone‐based peer support combined with face‐to‐face group sessions would significantly improve postoperative health‐related quality of life was not supported. We observed significant improvement in patients' quality of life after implantation in both groups, which was consistent with other studies (Lopez‐Villegas et al, ; Udo et al, ). However, we found that peer support was effective in improving patients' negative emotions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The primary hypothesis that a telephone‐based peer support combined with face‐to‐face group sessions would significantly improve postoperative health‐related quality of life was not supported. We observed significant improvement in patients' quality of life after implantation in both groups, which was consistent with other studies (Lopez‐Villegas et al, ; Udo et al, ). However, we found that peer support was effective in improving patients' negative emotions.…”
Section: Discussionsupporting
confidence: 92%
“…In the process of peer support, patients can build friendships, exchange information, learn to accept their own disease status, learn self‐care, and understand their situation better through comparisons with others. Patients undergoing pacemaker implantation experience changes in physical, psychological, social and other aspects of their lives (Barros & Silva, ; Ghojazadeh et al, ; Lopez‐Villegas, Catalan‐Matamoros, Robles‐Musso, & Peiro, ; Tagney, ). For pacemaker patients, peer support might help them get through this difficult process.…”
Section: Introductionmentioning
confidence: 99%
“…Between October 2012 and November 2013, a total of 89 patients were recruited in the Poniente Hospital (Almeria, Spain) for the original randomised controlled trial with a pre-planned follow-up of one year. Patient demographics, inclusion and exclusion criteria, operative details and outcomes have been reported previously [23,24].…”
Section: Setting and Patientsmentioning
confidence: 99%
“…The study sample size was previously described in detail [23,24], estimated to be 90 patients (45 per group) in the main study variable (EQ-5D utilities) between the groups, assuming a standard deviation of 0.20, an alpha error of 0.05 and a power of 0.80.…”
Section: Setting and Patientsmentioning
confidence: 99%
“…(15). Helserelatert livskvalitet viser seg å vere lik for dei med ordinaere kontrollar og dei med TM, og livskvaliteten betrar seg over tid i begge gruppene etter implantasjonen (4).…”
Section: Meir Tilfredse Pasientarunclassified